Inhibition of in vitro NZB antibody responses by cyclosporine. - Pisetsky, D S (1988)
To characterize functional abnormalities of B cells in murine autoimmunity, the effect of cyclosporine (CsA) on antibody responses of NZB and control BALB/c spleen cells was investigated in vitro. Under conditions of high cell density, both NZB and BALB/c spleen cells spontaneously produced IgM and IgM anti-DNA, although NZB responses were greater in magnitude and demonstrated at lower cell densities. In cultures at 5 x 10(6) cells/ml, CsA preferentially inhibited anti-DNA production by cells of both strains. However, to achieve similar levels of inhibition of both responses, significantly higher concentrations of CsA were required for cultures of NZB compared to BALB/c cells. These results support previous experiments indicating enhanced sensitivity to CsA as a pharmacological marker of autoantibody producing B cells. They further suggest that B cell activation in certain forms of autoimmunity may be associated with decreased sensitivity to immunosuppressive agents.